2003
DOI: 10.1016/s0165-4608(03)00199-7
|View full text |Cite
|
Sign up to set email alerts
|

Insertion (21;8)(q22;q22q22): a masked t(8;21) in a patient with acute myelocytic leukemia

Abstract: could not be determined without molecular analysis. This abnormality is considered a masked type of translocation 8;21.-2 -

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Recent studies have confirmed that spatial proximity of heterogenous chromosomes is more likely to cause chromosomal translocations, and the translocation-prone chromosomes are frequently located towards the nuclear center [11,12]. Abnormal karyotypes of AML-M2 have been largely studied using traditional cytogenetic analysis, reverse transcription-polymerase chain reaction (RT-PCR), and fluorescent in situ hybridization (FISH) techniques [13][14][15]. However, the three-dimensional (3D) spatial positions of chromosome 21 and chromosome 8 from AML-M2 patients are still rarely researched.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have confirmed that spatial proximity of heterogenous chromosomes is more likely to cause chromosomal translocations, and the translocation-prone chromosomes are frequently located towards the nuclear center [11,12]. Abnormal karyotypes of AML-M2 have been largely studied using traditional cytogenetic analysis, reverse transcription-polymerase chain reaction (RT-PCR), and fluorescent in situ hybridization (FISH) techniques [13][14][15]. However, the three-dimensional (3D) spatial positions of chromosome 21 and chromosome 8 from AML-M2 patients are still rarely researched.…”
Section: Introductionmentioning
confidence: 99%
“…However, the three-dimensional (3D) spatial positions of chromosome 21 and chromosome 8 from AML-M2 patients are still rarely researched. [15]/46,XY [5] 200 40…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the t(8;21)(q22;q22) is a common chromosomal change in diploid AML accompanied by loss of sex chromosomes, which correlates with a favorable prognosis 24–26. However, the incidence of t(8;21) is rare in near-tetraploid patients t(8;21)(q22;q22) 24,25,27. Herein, we have reported three novel cases (Cases 5, 6, and 7) of near-tetraploidy AML with double t(8;21)(q22;q22).…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of this kind of rearrangement, documented or presumed, among AML patients with the 5ЈRUNX1/ 3ЈCBFA2T1 fusion gene ranges from 1% to 8.5% (Grimwade et al, 2002;Gamerdinger et al, 2003), but it must be considered that these cryptic anomalies could be overlooked by conventional cytogenetics. To date, seven cases showing ins(21;8) and four cases with ins(8;21) have been described (Kazama et al, 1996;Harrison et al, 1999;Taviaux et al, 1999;Yamazaki et al, 2000;Urioste et al, 2002;Gamerdinger et al, 2003;Onozawa et al, 2003; Table 1). However, a detailed breakpoint characterization of the insertion event has never been attempted.…”
mentioning
confidence: 99%